The experience and attitude of TMU faculty and researchers toward predatory journals and research productivity (Journal of EAHIL, 2021)
A questionnaire related to journal submission was sent to researchers for a 2-week period to investigate the submission status as well as the problems faced by Taipei Medical University faculties and researchers. This study has two major findings including the Experience of predatory journal and Calculations of academic performance point and discuss about users’ cognition and their needs from the library and the university, as well as the library policy and services related to predatory journals. It is authors’ hope that the research results can serve as reference for other medical libraries planning to provide relevant services.